Lectures de The Lover’s Melancholy de John Ford (1629) : théâtre et mélancolie - Claire Gheeraert–Graffeuille; Athina Lavabre-Efstathiou (Etudes Epistémè)
First performed at the Blackfriars in 1629, John Ford’s The Lover’s Melancholy lends itself to various interpretations. This paper offers two readings. The first one focuses upon the central theme of melancholy and also considers the « Burtonian voices » in the play. Each one of Ford’s characters suffers from this black humour whose most acute forms are cured by means of a play-within-a play. The second reading takes a close look at the dramaturgical devices upon which the dramatist bases his therapy. Truly cathartic, the inset play sets in motion the final return to a harmonious state of mind and politics.